Electroconvulsive Therapy in the Czech Republic. Issue 2 (June 2018) - Kalisova, Lucie; Madlova, Katerina; Albrecht, Jakub; Michalec, Jiri; Kubinova, Marketa; Raboch, Jiri
Abstract : Objectives: Electroconvulsive therapy (ECT) is effective in the treatment of severe psychiatric disorders. Electroconvulsive therapy is applied to almost 1 million patients every year around the world. The aim of this study was to monitor the use of ECT in psychiatric facilities for adults in the Czech Republic (CR) in 2014 and to describe the national practice. Methods: A 14-item questionnaire was sent to all Czech inpatient psychiatric facilities that provide ECT, with the aim of getting a detailed picture of the use of ECT in the CR. The questionnaire assessed the technical background for using ECT in each center, along with indications for the treatment, the procedure, and the manner of documenting and monitoring adverse effects. The data obtained were supplemented with information about national legal and ethical regulations as well as historical background. Results: Electroconvulsive therapy is used in 26 centers across the CR. More than 1000 patients were treated with ECT in 2014. All centers use instruments delivering brief pulse stimuli, monitoring electroencephalogram and electrocardiogram. All patients have to be indicated for this treatment, which is a decision the patient's psychiatrist makes. All patients have to sign an informed consent form, excluding a situation where the patient's life is endangered. Somatic state is assessed in all patients. Bitemporal electrode placement is the preferred option in all centers. Conclusions: This article covers detailed information about the use of ECT in the CR. The results will be used to harmonize national practice and reduce the stigma associated with this method in the CR. Abstract : Supplemental digital content is available in the text.